Bimodal expression of Wnt5a in the tooth germ: A comparative study using in situ hybridization and immunohistochemistry - Sunohara, Masataka; Morikawa, Shigeru; Asada, Naomi; Suzuki, Kingo (Annals of Anatomy - Anatomischer Anzeiger, 2022)
•Mesenchymal cells undergo bimodal expression of Wnt5a during tooth development.•Undifferentiated mesenchymal cells express abundant Wnt5a mRNA but few proteins.•Apical accumulation of Wnt5a proteins occurs in differentiating odontoblasts about at E18.5. [Display omitted] During tooth development, Wnt5a, a member of the noncanonical Wnt ligand, is expressed prominently in the dental mesenchyme. However, the spatiotemporal profiles of Wnt5a protein production and distribution in tooth germs are largely unknown, which impairs elucidation of the Wnt5a-mediated regulatory mechanism of tooth development. We performed analyzes of the spatiotemporal expression of Wnt5a in embryonic tooth germs (E11.5–E18.5) by using in situ hybridization and immunohistochemistry in parallel. The developmental stages of the embryonic tooth germs were determined by HE staining. In order to compare the spatiotemporal distribution patterns of Wnt5a mRNA-expressing cells and those of Wnt5a protein-expressing cells, serial frontal sections of paraffinized mouse embryo heads were used for the analyzes. When needed, the immunohistochemistry images were subjected to digital detection analysis of Wnt5a immunostaining signal using the WinROOF 2018 Ver. 4.19.0 image processing software program. Throughout the developmental process, cells expressing Wnt5a mRNA were found in various tissues including the dental follicle, dental papilla, inner and outer enamel epithelium, stratum intermediate, and stellate reticulum. However, odontoblasts differentiating and polarizing at E18.5 were the only cells representing an accumulation of Wnt5a protein in the apical region of the odontoblast process. The Wnt5a protein was undetectable in undifferentiated mesenchymal cells as well as any other cells positive for Wnt5a mRNA. Differentiating odontoblasts execute Wnt5a expression, the mode of which is distinct from that executed by the other cells constituting tooth germ. Change of the mode of Wnt5a expression begins to take place in the mesenchymal cells by E18.5, starting the elongation of the cytoplasmic process.